Regulation of cardiac miR‐208a, an inducer of obesity, by rapamycin and nebivolol. (18th September 2015) - Gul, Rukhsana; Mahmood, Abuzar; Luck, Christian; Lum‐Naihe, Kelly; Alfadda, Assim A.; Speth, Robert C.; Pulakat, Lakshmi
Abstract : Objective: Resistance to obesity is observed in rodents and humans treated with rapamycin (Rap) or nebivolol (Neb). Because cardiac miR‐208a promotes obesity, this study tested whether the modes of actions of Rap and Neb involve inhibition of miR‐208a. Methods: Mouse cardiomyocyte HL‐1 cells and Zucker obese (ZO) rats were used to investigate regulation of cardiac miR‐208a. Results: Angiotensin II (Ang II) increased miR‐208a expression in HL‐1 cells. Pretreatment with an AT1 receptor (AT1R) antagonist, losartan (1 μM), antagonized this effect, whereas a phospholipase C inhibitor, U73122 (10 μM), and an NADPH oxidase inhibitor, apocynin (0.5 mM), did not. Ang II‐induced increase in miR‐208a was suppressed by Rap (10 nM), an inhibitor of nutrient sensor kinase mTORC1, and Neb (1 μM), a 3rd generation β‐blocker that suppressed bioavailable AT1R binding of 125 I‐Ang II. Thus, suppression of AT1R expression by Neb, inhibition of AT1R activation by losartan, and inhibition of AT1R‐induced activation of mTORC1 by Rap attenuated the Ang II‐induced increase in miR‐208a. In ZO rats, Rap treatment (750 μg kg −1 day −1 ; 12 weeks) reduced obesity despite similar food intake, suppressed cardiac miR‐208a, and increased cardiac MED13, a suppresser of obesity. Conclusions: Rap and Neb suppressed cardiac miR‐208a. Suppression of miR‐208a and increase in MED13 correlated with attenuated weight gain despite leptin resistance.